A pressure-amplifying framework material with negative gas adsorption transitions - Krause, Simon; Bon, Volodymyr; Senkovska, Irena; Stoeck, Ulrich; Wallacher, Dirk; Toebbens, Daniel M.; Zander, Stefan; Pillai, Renjith S.; Maurin, Guillaume; Coudert, Francois-Xavier; Kaskel, Stefan (Nature, 2016)
Adsorption-based phenomena are important in gas separations, such as the treatment of greenhouse-gas and toxic-gas pollutants, and in water-adsorption-based heat pumps for solar cooling systems. The ability to tune the pore size, shape and functionality of crystalline porous coordination polymers - or metal-organic frameworks (MOFs) - has made them attractive materials for such adsorption-based applications. The flexibility and guest-molecule-dependent response of MOFs give rise to unexpected and often desirable adsorption phenomena. Common to all isothermal gas adsorption phenomena, however, is increased gas uptake with increased pressure. Here we report adsorption transitions in the isotherms of a MOF (DUT-49) that exhibits a negative gas adsorption; that is, spontaneous desorption of gas (methane and n-butane) occurs during pressure increase in a defined temperature and pressure range. A combination of in situ powder X-ray diffraction, gas adsorption experiments and simulations shows that this adsorption behaviour is controlled by a sudden hysteretic structural deformation and pore contraction of the MOF, which releases guest molecules. These findings may enable technologies using frameworks capable of negative gas adsorption for pressure amplification in micro- and macroscopic system engineering. Negative gas adsorption extends the series of counterintuitive phenomena such as negative thermal expansion and negative refractive indices and may be interpreted as an adsorptive analogue of force-amplifying negative compressibility transitions proposed for metamaterials.
CRIS-Team Scopus Importer:2023-03-20